A relação trabalho e saúde dos psicólogos hospitalares de João Pessoa/ Paraíba - Alves, Simone Salviano (2014)
The Hospital Psychology, as a field of understanding and treating of psychological aspects related to illness has as its focus the care of the hospitalized patient. In this sense, the Hospital Psychologist assumes many responsibilities and they are constantly exposed to the characteristics risk of work in the hospital. Considering that the Work occupies a central place in human beings lifestyle and Society in general and therefore relates intimately of workers’ health, the present study aimed to analyze the relationship between work and health of Hospital Psychologists of João Pessoa - Paraíba. As the specific objectives were listed: to characterize the content of Hospital Psychologists job; to know the conditions and organization of the work of these professionals, highlighting the sources of pain and pleasure in work situations of these professionals, and finally verify relationships between the characteristics of conditions and organization of work of Hospital Psychologists and their state of health. Starting from a non - experimental design, exploratory and descriptive. As instruments of data collection were used the Health and Work Survey (INSAT) and an individual semi - structured interview. The research involved 40 Hospital Psychologists, male and female, active in public Hospitals in the city of João Pessoa, Paraíba, located in Northeastern Brazil. The INSAT responses were stored in the program Statistical Package for Social Science for Windows (SPSS, version 20.0), which were subjected to the treatment of descriptive and inferential statistics. On the other hand, researches obtained through semi - structured individual interviews were analyzed using thematic content analysis. To analyze the complex relationship between work and health professionals focus we interlaced the data from the two instruments, outlining a discussion based on our understanding of work and health, the relationship between these two elements and also our guiding approaches, which were the Psychodynamics of Work and Ergonomics of Activity. The produced results show mainly that Hospital Psychologists constantly experiencing pain and pleasure in work situations. Also evidence of physical and mental health problems affecting these professionals that are directly related to the organization and the working conditions in which they live. Hopefully, by the results of this study contribute to the production and popularization of knowledge about Hospital Psychology and aspects involving the professional of this category, especially those related to your work and health.